An Analysis of the Preservation Efforts of the Hongde Sport Association Lion Dance Club in Promoting Chinese Culture in Surabaya - Vania Cindy; Elisa Churota’ayun; Xinrui Liu; Maria Apriana (Universitas Negeri Surabaya, 2026)
Barongsai is a traditional Chinese performing art that carries strong cultural, spiritual, and social values. In Surabaya, Hongde Sport Association is one of the active clubs that strives to preserve the existence of barongsai through various artistic and cultural initiatives. This study aims to analyze the preservation efforts of Barongsai Club Hongde Sport Association and its role in promoting Chinese culture in Surabaya. This research employs a descriptive qualitative method with data collected through interviews, observations, and documentation. The results indicate that Hongde Sport Association carries out cultural preservation through regular training, member regeneration, participation in cultural events, community collaboration, and performance adaptation to societal developments. Moreover, the club functions as a cultural medium that introduces Chinese cultural values to the public through performances and educational activities. The conclusion of this research is that Hongde Sport Association contributes significantly to sustaining the existence of barongsai and strengthening Chinese cultural identity in Surabaya.